2017
DOI: 10.26740/jpps.v6n1.p1212-1217
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Fisika Berbasis Kontekstual Dengan Mengintegrasikan Kearifan Lokal Untuk Meningkatkan Pemahaman Konsep Fisika Pada Mahasiswa

Abstract: This research is a development research that develops teaching materials physics based contextual by integrating local wisdom. To further this research as the basis for the development of textbook physics of high economic value. This study intends to improve the mastery of concepts of physics students. Teaching materials developed using models of R & D with develop model used is a model development Borg & Gall (1985) and Kemp and Dayton (1985), which consists of; (1) research and data collection throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
22

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 0 publications
0
15
0
22
Order By: Relevance
“…Local wisdom is a set of knowledge, values, behaviours, and the way to behave towards certain objects and events in their environment that the goodness and the truth are accepted. The integration of local wisdom in physics teaching materials will make it easier for students to understand and accept physics lesson [18]. However, the integration of local wisdom to physics module is lacked to conduct.…”
Section: Introductionmentioning
confidence: 99%
“…Local wisdom is a set of knowledge, values, behaviours, and the way to behave towards certain objects and events in their environment that the goodness and the truth are accepted. The integration of local wisdom in physics teaching materials will make it easier for students to understand and accept physics lesson [18]. However, the integration of local wisdom to physics module is lacked to conduct.…”
Section: Introductionmentioning
confidence: 99%
“…Two articles for students of junior high school (Maskhuliyah & Bungkang, 2017;Lepiyanto, 2011), 13 articles for senior high school (Sujanem, 2012;Sufinah et al, 2013;Landriany, 2014;Susilo et al, 2014;Tampubolon et al, 2015); and 50 articles for university students (Zuchdi et al, 2010;Parmin & Peniati, 2012;;Tannir & Al Hroub, 2013;Al Azri. & Al Rashidi, 2014;;Celik, 2014;Novian et al, 2014;Khaimar, 2015;Satriawan & Rosmiati, 2016); Fadilah et al, 2016;Nisrina et al, 2016;Komang et al, 2017;Maskhuliyah et al, 2017;Nihayah et al, 2018) as shown in Figure 4. The literature selected is mostly articles for students, so that the findings obtained are wider in scope than the findings for junior and senior high school students.…”
Section: Educational Stagementioning
confidence: 96%
“…Selain itu pemberian contoh yang nyata dan sesuai dengan isu permasalahan yang dihadapi dalam kehidupan sehari-hari juga dapat meningkatkan pemahaman dan motivasi belajar mahasiswa. Hal ini diungkapkan oleh (Satriawan, 2016) yang menyatakan bahwa mahasiswa sangat tertarik untuk mempelajari materi karena contoh-contoh yang disajikan adalah isu nyata dalam kehidupan sehari-hari.…”
Section: Pendahuluanunclassified